The effect of porang coating application and storage time on the characteristics of Kintamani Siamese Oranges - Luh Suriati; Ni Made Ayu Suardani Singapurwa; Aida Firdaus Muhamad Nurul Azmi; Rovina Kobun; I Wayan Widiantara Putra; Putu Ajus Raditya Putra (EDP Sciences, 2024)
Kintamani Siamese Orange is one of Indonesia's leading fruits with a distinctive taste, sweet with a slight sourness. One of the efforts to increase the shelf life of Kintamani Siamese Orange is by coating using edible materials. The edible coating can be made using renewable natural materials, one of these natural ingredients is porang starch. Porang coating is a thin layer made from glucomannan porang tubers. The application of the coating is needed to improve the appearance and maintain the quality of Kintamani Siamese citrus fruits. The motive of this examination was to decide the impact of porang coating type and storage time on the characteristics of Kintamani Siamese orange. This observation used a factorial randomized group design with two treatment factors, namely the type of porang coating (without coating, coating, and nanocoating), and the storage time of oranges (5 days, 10 days, 15 days). The best characteristics of Kintamani Siamese Orange were obtained from the treatment of porang nanocoating application with criteria of fruit weight shrinkage value of 12.47%, acidity (pH) of 4.30, total dissolved solids of 15.77ºBrix, moisture content of 94.21%, vitamin C of 78.55 and the amount of damaged fruit of 20.00% up to 5 days storage.